Berken plow and intercropping with pigeon pea ameliorate degraded soils with a hardpan in the Ethiopian highlands - Fenta, H.M.; Hussein, M.A.; Tilahun, Seifu A.; Nakawuka, Prossie; Steenhuis, Tammo S.; Barron, Jennie; Adie, Aberra; Blümmel, Michael; Schmitter, Petra S. (Elsevier, 2022)
Closing the yield gap and enhancing efficiency in rainfed maize production systems in Ethiopia requires urgent action in increasing the productivity of degraded agricultural land. The degradation of land through continuous compaction and decline in the organic matter has resulted in a wide-spread formation of a hardpan that restricts deep percolation, prevents plant root development, and, ultimately can lead to increased erosion. Studies exploring practical low-cost solutions to break the hardpan are limited in Ethiopia. The main objective was to evaluate soil mechanical (i.e. modified plow or Berken plow) or biological intervention (i.e. intercropping with pigeon pea) effectiveness to enhance soil water management and crop yield of rainfed maize systems whilst reducing soil erosion and runoff. Five farm fields, each including four plots with different tillage treatments, were monitored during two rainy seasons in 2016 and 2017. The treatments were: (i) farmers practice under conventional (CT) tillage; plots tilled three times using an oxen driven local plow Maresha, (ii) no-till (NT), (iii) Berken tillage (BT), plots tilled three times using an oxen pulled Berken plow, and (iv) biological (CT + Bio), taprooted pigeon pea intercropped with maize on plots conventionally tilled. Results showed that mean tillage depth was significantly deeper in the BT (28 cm) treatment compared to CT and CT + Bio (18 cm) treatments. Measured soil penetration resistance significantly decreased up to 40 cm depth under BT and maize roots reached 1.5 times deeper compared to roots measured in the CT treatment. Under BT, the estimated water storage in the root zone was estimated at 556 mm, 1.86 times higher compared to CT, 3.11 times higher compared to NT and 0.89 times higher compared to CT + Bio. The positive effects on increased water storage and root development resulted in an average increase in maize grain (i.e. 15%, 0.95 t ha- 1 ) and residual above ground biomass (0.3%, 6.4 t ha- 1 ) leading to a positive net benefit of 138 USD ha- 1 for the BT treatment compared to the CT treatment. The negative net benefit obtained under CT and CT+Bio was mainly related to the high labor cost related to plowing, weeding, planting, and fertilizer application whilst in the NT this was related to the significantly lower maize yields. The positive effects in the BT treatment, and to some extent the CT+Bio treatment show great potential for smallholder rainfed maize systems where degraded soils with hardpans and high variability in rainfall prevail.